Diseño y aplicación de una batería multidimensional de indicadores de rendimiento para evaluar la prestación competitiva en el fútbol de alto nivel - Valez Vazquez, A.; Areces Gayo, A.; Blanco Pita, H.; Arce Fernandez, C. (Revista Internacional de Ciencias del Deporte, 2011)
The aim of the present study was the design and application of a multidimensional battery comprising five performance indicators: Play Initiative Index (PII), Physical Load Index (PLI), Offensive Play Volume Index (OPVI), Offensive Play Precision Index (OPPCI) and Offensive Play Progression Index (OPPGI), aimed at evaluating the competitive performance of top-level football teams and differentiating the performance profile obtained by winning teams and losing teams during matches. 67 belonging to the group phase of the Uefa Champions League matches were analysed in the 2009-10 season. Statistical analyses of mean comparisons and logistic regression between winners and losers, made it possible to conclude that winning teams show statistically higher values in four of the five performance indices used (PII, OPVI, OPPCI and OPPGI), with PII (p<.001), OPPCI (p<.001) and OPVI (p<.001) being the indices with greatest descriptive power. Nonetheless, no statistically significant differences were obtained between both groups in the PLI index (p>.05). The multidimensional battery of performance indicators proposed herein may prove to be highly useful tool for evaluating and predicting performance in top-level football.